21.63% industrial screen‐printed multicrystalline Si solar cell. Issue 3 (14th February 2017) - Zheng, P.; Xu, J.; Sun, H.; Zhang, F.; Guo, Y.; Pan, H.; Chan, K. S.; Jin, J.; Wang, H.; Chen, W.; Zhang, X.; Jin, H.
Abstract : In this paper, we demonstrate industrially feasible large‐area solar cells achieving energy conversion efficiency up to 21.63% on p‐type boron doped multicrystalline Si wafers. Advanced light trapping, passivation and hydrogenation technology are used to achieve excellent light absorption with very low surface recombination velocity. The bulk lifetime of the multi‐crystalline Si wafers used for the fabrication exceeds 500 μs after optimized gettering and hydrogenation processes. The high bulk lifetime and excellent surface passivation enable V oc to exceed 670 mV. The metallization process is carried out by screen printing and firing in a conventional belt furnace. Detailed performance parameters and quantum efficiency of the cells will be illustrated in the paper. In addition, free energy loss analysis and cell simulation are also performed using the control parameters measured during cell fabrication processes. Abstract : Multicrystalline silicon is the dominant material for solar cell manufacturing due to its cheap production cost. Despite impressive technological progresses over the last few years, the practical efficiency limit for multicrystalline silicon solar cells remains unknown. In this Letter, Zheng et al. present industry‐grade multicrystalline silicon solar cells with efficiency >21.5%, based on a passivated emitter rear contact (PERC) structure and optimized processing conditions for multicrystalline silicon.